International Research Collaboration: A Working Model - Haddow, Gaby (Nanyang Technology University, 2013)
Research collaboration has the potential to increase the productivity of researchers and the exposure of their work. International collaboration also develops personal networks across diverse cultures and contributes to an appreciation of different approaches to issues experienced by those in the field. In the current higher education environment, where productivity is an imperative and the expectations of academics are rising, effective research collaboration enables researchers to share the workload while enhancing their own research skills and performance. This paper discusses the nature of research collaboration, focusing on international collaboration. It reviews the literature about the drivers and motivations behind collaboration, as well as the key benefits. Research and commentary about international research collaboration and measures for assessing successful collaboration,is discussed. In addition, the main findings relating to barriers and other considerations in collaborative activities are reviewed. The paper concludes by describing a working model of international research collaboration in the library and information science field. Based on the author’s involvement in two international research collaborations, links are drawn between research findings and a lived experience.